Surviving and Having a Healthy Baby Are Low Bars for Childbirth: Women Have the Right to Expect Much More. Issue 2 (March 2020) - Callister, Lynn Clark
Abstract : Lack of respectful maternity care is an ongoing issue in the United States and around the world. Our global health nursing expert, Dr. Callister, covers recent studies and the recommendations for improvement from the World Health Organization.